Home Numeracy Experiences and Children's Math Performance in the Early School Years. - LeFevre, Jo-Anne; Skwarchuk, Sheri-Lynn; Smith-Chant, Brenda L.; Fast, Lisa; Kamawar, Deepthi; Bisanz, Jeffrey (Canadian Journal of Behavioural Science, 2009)
Children's numerical competence in kindergarten is highly predictive of their acquisition of mathematics in Grade 1 and Grade 2, suggesting that experiences at home before schooling are important in understanding how numeracy develops. In this study, the mathematical skills of 146 children in Kindergarten. Grade 1, and Grade 2 were correlated with the frequency with which parents reported informal activities that have quantitative components such as board and card games, shopping, or cooking. Effect sizes were consistent with research relating home literacy experiences to children's vocabulary. The present research supports claims about the importance of home experiences in children's acquisition of mathematics. Reprinted by permission of the publisher.